Measurement of neutron production from an ¹⁸O target for the production of radioactive-ion beams at iThemba LABS - Ngcobo, Phumlani Zipho (Department of Physics, 2019)
iThemba LABS, in the South African Isotope Facility (SAIF) project, proposes to produce radioactive ion beams by the fission of uranium. A natural way to fission uranium is to use high-intensity proton beams from a cyclotron. However, neutron-induced fission gives enhanced production of neutron-rich fission fragments compared to proton-induced fission, thus there is a need to find efficient ways of producing neutrons from protons. Beryllium targets have been suggested, but increasing the proton beam current to achieve higher fission rates could lead to cooling problems. Cooling might be achieved in a natural way by using enriched water as a converter, but ¹⁶O is a poor neutron converter compared with ⁹Be. An alternative would be to use water enriched in ¹⁸O. With no data available for ¹⁸O above 25 MeV, this necessitated the measurement of neutron yields from the ¹⁸O(p,xn) reactions between 30 and 66 MeV. Quasi-monoenergetic neutron spectra were therefore measured at proton energies of 66; 54; 42 and 30 MeV on a 2.03 mm thick H₂¹⁸O water target using the time of flight (ToF) technique at 0˚ and 16˚. Neutron energy spectra from a ⁷Li (2.5 ± 0.5 mm thick) target were also measured at the same energies to validate the H₂¹⁸O measurements. The spectra deduced at these energies were used to simulate the neutron fluence spectra from a stopping-length H₂¹⁸O target and were compared with the measured neutron fluence spectra from a thick target of 40.0 ± 0.1 mm at 0˚ and 16˚, using a proton beam of 62 MeV. The neutron differential cross sections, dσ(E)/dΩ for the ¹⁸O(p,n) reactions at 66; 54; 42 and 30 MeV were derived and compared to those of ⁷Li(p,n) and ⁹Be(p,n). The cross sections of ⁷Li and ⁹Be are higher than those of ¹⁸O between 20 MeV and 50 MeV at 0°. At above 60 MeV, the ⁷Li target produces double the amount of neutrons produced by ¹⁸O and ⁹Be targets, but importantly ¹⁸O produce neutrons more than ⁹Be. The ¹⁸O(p,xn) neutron cross sections (d²σ(E)/dΩdE in mb/MeV/sr) from the thick stopping-length target (40 mm) were compared to the corresponding cross sections of ⁹Be thick stopping-length target (24.1mm). Conclusively, on average, the ¹⁸O neutrons cross sections are half those of ⁹Be.